The system of stimulation of work in modern conditions - Legostayeva, A.A.; Orynbassarova, Ye.D.; Vladimirov, Zh. (BUKETOV BUSINESS REVIEW, 2020)
Оbject: is to develop scientifically based recommendations for improving the system of labor incentives in modern conditions based on a comprehensive analysis and evaluation of the system. Methods: When writing the article, the following methods were used: methods of scientific analysis, synthesis, and structural analysis. Findings: It is revealed that in modern conditions, the human resources potential of the modern economy is the most important strategic factor affecting the country's competitive advantages in the world. In the course of the study, the factors that influence the formation of the labor incentive system were classified. the main principles of building an effective motivation system in modern conditions are revealed, its types are considered, and modern theories of motivation are analyzed. Conclusions: In the course of the study, the authors concluded that it is necessary to apply more flexible approaches to determining the level of the basic salary and the variable part of the salary, the need to link the salary with the final performance indicators of both the individual employee and the entire structural unit, as well as the enterprise as a whole. A classification of factors that influence the formation of the labor incentive system is proposed, including two groups: external (objectively existing and independent of the company's management) and internal (formed and dependent on the company's management).